The capacitated location routing problem: review of literature - Escobar, John Willmer; Linfati, Rodrigo; Jaimes, Wilson Adarme (Universidad Pedagógica y Tecnológica de Colombia, 2015)
In this paper, we review the state of the art of the published solution methods for combined problems of location and routing with capacity constraints (CLRP). The CLRP has several practical application in topics related to transportation. We have proposed the following classification scheme based on the solution method: (1) Constructive Heuristics Algorithms, (2) Heuristic Algorithms Based on Clusters, (3) Heuristic Algorithms Based on Trajectory,. (4) Heuristic Algorithms Based on Population, (5) Combined Heuristic Algorithms, (6) Exact Methods. Special emphasis is placed on the fortress and on the lack of each published method, identifying research opportunities in the context of the real application of the problem.